Lateral Stress Sensor Based on an In-Fiber Mach–Zehnder Interferometer and Fourier Analysis - Xiujuan Yu; Dan Bu; Xuefeng Chen; Jintao Zhang; Shengchun Liu (IEEE Photonics Journal)
A novel lateral stress sensor based on a compact in-fiber Mach–Zehnder interferometer (MZI) and Fourier analysis is proposed and demonstrated. The in-fiber MZI is formed by cascading two offset splicing joints. The interference occurs between the copropagating fundamental core and cladding modes. The influence of offset value on the performance of modal interferometer, including the extinction ratio and insertion loss, has been experimentally investigated. The spatial spectra of the proposed in-fiber interferometers with different interference lengths are analyzed by Fourier transform. An in-fiber interferometer with an interference length of 30 mm has been fabricated for lateral stress measurement. The performance of the lateral stress sensor is investigated in a spatial frequency domain by Fourier transform of the corresponding transmission wavelength spectra. The responses of intensity peaks to different lateral stresses are analyzed in the spatial frequency domain. The sensitivity of the in-fiber MZI-based lateral stress sensor is as high as 0.00455/ $μ\text{m}$ . The proposed lateral stress sensor possesses the advantages of simple and compact structure, high sensitivity, ease of manufacture, and low cost, and it will provide a simple and effective method for detecting the slight fiber deformation induced by lateral stress.